Tatsumi [videorecording (DVD)] - Khoo, Eric, 1965-; Bessho, Tetsuya, 1965-; Tatsumi, Yoshihiro, 1935-2015; Tatsumi, Yoshihiro, 1935-2015 (KimStim collection., 2013)
"Tatsumi celebrates the life and work of Yoshihiro Tatsumi--a manga pioneer who transformed the genre with cinematic inspiration and psychological depth. His youthful passion for comics blossomed with a means to support his family in postwar Osaka--but he became tired of producing whimsical children's tales. In 1957 Tatsumi redefined the manga landscape with an adult-oriented genre that grappled with the darker aspects of Japanese life, which he called gegeka (dramatic pictures). In Tatsumi, Singaporean filmmaker and former comic artist Eric Khoo ... brings Tatsumi's 2010 graphic memoir A drifting life and five of his classic stories to vivid, stunning life"--Container.